PERSEPSI GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN MATEMATIKA DI SMP SEKOLAH SAMPEL PISA - Richatul Asmah; Kintoko Kintoko (Jurnal Karya Pendidikan Matematika, 2023)
This study aims to determine teacher perceptions regarding critical thinking skills in learning mathematics at SMP Mataram Kasihan as a PISA sample school. This research was conducted in November 2022. This research is a qualitative descriptive study. The critical thinking approach in the process of learning mathematics is the focus of this research. The data were taken from an interview with a mathematics teacher at the PISA sample junior high school. Data collection is done by interview, observation. Data analysis used descriptive analysis and the literature-led method. The results of this study showed that: teachers view students as having positive perceptions of students' critical thinking skills by using critical thinking. The teacher's positive perception includes the teacher's perception of students' critical thinking skills.